1987
DOI: 10.1002/art.1780301207
|View full text |Cite
|
Sign up to set email alerts
|

Metacarpophalangeal arthropathy associated with manual labor (missouri metacarpal syndrome). clinical, radiographic, and pathologic characteristics of an unusual degenerative process

Abstract: We describe 7 manual laborers with painful, palpably enlarged metacarpophalangeal joints. Characteristic radiographic changes were joint space loss, prominent osteophytes, and cystic metacarpal heads most prominent in the second and third metacarpophalangeal joints. In 3 of 4 patients, joint biopsy specimens showed subsynovial fibrosis and villous hyperplasia. All 7 patients had similar backgrounds of heavy work demanding sustained gripping motions of both hands, for periods that exceeded 30 years. We designat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 33 publications
2
16
0
2
Order By: Relevance
“…Although studies have shown that OA at the thumb base is highly heritable in whites (4), both the thumb base and the MCP joints are also susceptible to large lever arm forces during power grip (25). Several studies have shown that OA in the MCP joints is associated with jobs that often require power grip (26,27). In a longitudinal study, Chaisson et al found that the association between grip strength and incident OA is stronger in the MCP joints than in more distal joints, especially among women (25).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have shown that OA at the thumb base is highly heritable in whites (4), both the thumb base and the MCP joints are also susceptible to large lever arm forces during power grip (25). Several studies have shown that OA in the MCP joints is associated with jobs that often require power grip (26,27). In a longitudinal study, Chaisson et al found that the association between grip strength and incident OA is stronger in the MCP joints than in more distal joints, especially among women (25).…”
Section: Discussionmentioning
confidence: 99%
“…9,18,19 The primary purpose of this article was to present a case of MCP joint OA associated with a manual labor occupation and, in doing so, familiarize chiropractors with the so-called Missouri metacarpal syndrome. 15 This article also serves to remind the chiropractic physician of the key differentials of MCP arthropathy, namely, hemochromatosis and CPPD crystal deposition disease.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few other studies describing similar cases were found in PubMed. [15][16][17] In a case series by Williams et al, 15 all 7 patients studied were male manual laborers (farmers, truck drivers, heavy machine operators, and a mason). Their ages ranged from 51 to 72 years, and all had engaged in heavy labor involving their hands for between 31 to 50 years.…”
Section: Manual Labor Mcp Arthropathymentioning
confidence: 99%
See 2 more Smart Citations